Role of Green Finance for Sustainable Environment So Far: A Bibliometric Analysis and Policy Framework - Nasim, Ismat (Pakistan Journal of Humanities and Social Sciences, 2023)
A bibliometric examination of green finance's contribution to environmental sustainability is the intended outcome of this work. The research also offers a policy framework for environmentally friendly financing. To produce the bibliometric analysis, we used proper keywords to sift through the Scopus database for relevant, peer-reviewed research articles published between 2008 and 2022 (Dec 2022). In this study, the titles, abstracts, keywords, frameworks, and headers of 444 relevant papers were screened using bibliographic coupling and text mining. The research used the scientific landscapes visualization tool for the analysis. Our evaluation provides a systematic account of the effectiveness of related works in the field of green finance. Authors, publications, and theoretical and topical contributions to the field are all revealed through bibliometric analysis. This paper provides a theoretical framework for future studies on the effects of green financing on sustainable environments. The interdependencies between different industries and how they might work together to protect the environment are also laid forth. Green finance plays a unique role in protecting the natural world. This work makes a contribution to the literature on green finance and sustainable environments by identifying theoretical clusters for future research on environmental performance. The paper also lays out the goals of the green finance policy framework.